Internal and External Factors in Tenth-Grade EFL Speaking Anxiety - RIando Nabatajoe; Ria Saraswati (Foremost Journal, 2026)
Speaking anxiety remains a barrier to oral participation in EFL classrooms because students must speak publicly while managing ideas, vocabulary, grammar, pronunciation, and peer evaluation. This qualitative study investigated internal and external factors contributing to speaking anxiety among 15 tenth-grade students at a private senior high school in Jakarta. Data were collected through semi-structured interviews and analyzed through data reduction, data display, and conclusion drawing. The analysis used a framework covering internal factors, namely lack of self-confidence, fear of making mistakes, shyness, and motivation, and external factors, namely limited vocabulary, peer responses, lack of preparation, and grammatical errors. The findings show that speaking anxiety was produced by interacting psychological, linguistic, and social conditions. Internally, students lacked confidence, feared errors, felt embarrassed when observed, and had unstable motivation. Externally, anxiety was intensified by vocabulary gaps, peer laughter or comparison, spontaneous tasks, limited preparation time, and grammar uncertainty. These factors formed an avoidance cycle that reduced practice and confidence. The study implies that teachers should design scaffolded, low-pressure speaking activities, normalize mistakes, provide preparation time, strengthen vocabulary use, and build a respectful peer culture.